Ethnic pluralism and the challenge of thematic curriculum implementation in Uganda - Amone, Charles (Informa UK Limited, 2019)
Uganda has been developing and revising its curricula since the time of British colonial rule. The latest revision of the primary education curriculum led to the introduction of the Thematic Curriculum in 2007. This curriculum requires the use of pupils' mother tongues as languages of instruction from Primary One to Three and then English from Primary Five to Seven. Primary Four is a transitional year. Several studies have indicated that the Thematic Curriculum has been a failure. Although various reasons have been advanced for the challenges of the Thematic Curriculum, the greatest setback seems to be ethnic pluralism. Using in-depth interviews with teachers, parents, education officials and pupils, I investigated how ethnic pluralism impeded the implementation of the Thematic Curriculum in Uganda. I found that most districts in Uganda are multi-ethnic and therefore multi-lingual making it difficult to choose the dominant mother tongue to use as a language of instruction. Even when the dominant language is identified, the pupils and teachers are in most cases from diverse ethnic and linguistic backgrounds. This study recommends the introduction of a national language to be used as medium of instruction at the lower levels of education in Uganda.